Long-term effects of lime and phosphogypsum on soil carbon and nitrogen and physical attributes under tropical no-till - da Costa, Claudio Hideo Martins; Wander, Michelle M.; Crusciol, Carlos Alexandre Costa [UNESP]; Ugarte, Carmen; Rigon, João Paulo Gonsiorkiewicz [UNESP]; Soratto, Rogério Peres [UNESP]; Calonego, Juliano Carlos [UNESP] (Wiley, 2021)
Lime and phosphogypsum applications are well-established practices in weathered soils, and their surface application under no-till (NT) can affect soil physical attributes and C and N fractions. This study determined the long-term (10-yr) effects of lime and phosphogypsum applications to the soil surface on soil C and N fractions of a tropical NT field. The experimental design was a randomized block with four treatments and four replications. The following treatments were applied in October 2002, November 2004, and October 2010, respectively: limestone (2,000 kg ha−1), phosphogypsum (2,100 kg ha−1), and limestone (2,000 kg ha−1) plus phosphogypsum (2,100 kg ha−1). In general, after 10 yr of liming, both alone and when associated with phosphogypsum, the cumulative crop straw inputs were increased at least 20% across the years, and the C fractions increased remarkably at different soil depths. Both treatments improved the SOC stocks by 24% (12.5–15.6 Mg ha−1) at 0.1–0.2-m soil depths and by 10% (30.6–33.8 Mg ha−1) at 0–0.2-m soil depths, and in general the soil aggregation at 0–0.4-m soil depths. However, the particulate C and N fractions were reduced at 0–0.05-m soil depth, suggesting a slight response to the transitory trend of soil organic C (SOC) depletion. Liming, both alone and when associated with phosphogypsum, overcame the transitory C pool depletion and improved soil aggregation, soil C fractions, and SOC stocks and could be considered an important factor that drives the sustainability of cropping systems under NT.